2010
DOI: 10.1007/s10637-010-9521-4
|View full text |Cite
|
Sign up to set email alerts
|

Salarin C, a member of the salarin superfamily of marine compounds, is a potent inducer of apoptosis

Abstract: The continuous emergence of new diseases and the development of drug-resistant cancers necessitate the development of new drugs with novel mechanisms of action. The richest marine source of natural anti-cancer products has been soft-bodied organisms that lack physical defenses against their predators, and hence rely on chemical defense mechanisms using cytotoxic secondary metabolites. Bio-guided (brine shrimp test) separation of CHCl(3)-CH(3)OH (1:1) extract from the Madagascar Fascaplysinopsis sp. sponge prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…These are secondary metabolites, derived by the repetitive condensation of acetate Anti-cancer Drugs -Nature, Synthesis and Cellunits or other short carboxylic acids catalyzed by multi-functional enzymes called polyketide synthases (PKSs) which is similar to fatty acid synthases [145]. Many polyketides suppress CML cell proliferation and induce apoptosis (Figure 3) (Table 6) [146][147][148][149][150][151][152][153][154][155].…”
Section: Polyketidesmentioning
confidence: 99%
“…These are secondary metabolites, derived by the repetitive condensation of acetate Anti-cancer Drugs -Nature, Synthesis and Cellunits or other short carboxylic acids catalyzed by multi-functional enzymes called polyketide synthases (PKSs) which is similar to fatty acid synthases [145]. Many polyketides suppress CML cell proliferation and induce apoptosis (Figure 3) (Table 6) [146][147][148][149][150][151][152][153][154][155].…”
Section: Polyketidesmentioning
confidence: 99%
“…27 Lovastatin was administered as a single 60 mM dose, at time 0, to cultures incubated in normoxia. Nocodozole was administered as a single 0.1 mM dose, at time 0, to cultures incubated in normoxia.…”
Section: Drug Treatmentmentioning
confidence: 99%
“…27 The study reported here was undertaken to deepen the effects of Salarin C on CML cells and in particular to establish whether the drug is active on CML cells selected in low oxygen and refractory to TKi. We determined the effects of salarin C: (a) on CML cell lines cultured in low oxygen; (b) on the maintenance of stem cell potential in cultures of cell lines as well as primary CML cells incubated in low oxygen; (c) on stem cell potential, when combined to IM.…”
Section: Introductionmentioning
confidence: 99%
“…Salarin C was by far more potent than salarins A and B and tulearin A [62]. In addition to the above salarins, we have isolated seven others (D–J) in minute amounts.…”
Section: Introduction To the Fascaplysinopsis Sp Metabolitesmentioning
confidence: 99%